2020
DOI: 10.7554/elife.61762
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy success in mice requires appropriate cannabinoid receptor signaling for primary decidua formation

Abstract: With implantation mouse stromal cells begin to transform into epithelial-like cells surrounding the implantation chamber forming an avascular zone called the primary decidual zone (PDZ). In mouse, the PDZ forms a transient, size-dependent permeable barrier to protect the embryo from maternal circulating harmful agents. The process of decidualization is critical for early pregnancy maintenance in mice and humans. Mice deficient in cannabinoid receptors, CB1 and CB2, show compromised PDZ with dysregulated angiog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Upon embryo implantation, stromal cells proximally surrounding the implantation chamber (i.e., S1p cells) exhibit proliferation and spreading. These cells differentiate and form the primary decidual zone (PDZ) on the afternoon of gestational day 5 [ 25 , 26 ]. Thus, the interaction between LE and S1p represents the uterine epithelial-stromal crosstalk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon embryo implantation, stromal cells proximally surrounding the implantation chamber (i.e., S1p cells) exhibit proliferation and spreading. These cells differentiate and form the primary decidual zone (PDZ) on the afternoon of gestational day 5 [ 25 , 26 ]. Thus, the interaction between LE and S1p represents the uterine epithelial-stromal crosstalk.…”
Section: Resultsmentioning
confidence: 99%
“…Upon embryo implantation, stromal cells proximally surrounding the implantation chamber (i.e., S1p cells) exhibit proliferation and spreading. These cells differentiate and form the primary decidual zone (PDZ) on the afternoon of gestational day 5 [ 25 , 26 ]. Gene ontology analysis showed that stress response, cell death, transport, cell cycle and proliferation, cell organization and biogenesis, developmental processes, protein metabolism, DNA metabolism and RNA metabolism were significantly enriched among differentially expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although both CNR1 and CNR2 are active in decidualization, CNR1 may have a more prominent role. Absence of CNR1 and CNR2 show compromised decidualization in mice in a CNR1-dependent manner validated through in-vitro studies 35 . Similarly, in our study, EM lesions (both UnD and DD) from mice lacking CNR1 showed significantly more DEGs (2088), compared to CNR2 (287) and WT (2).…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, CB1 deficiency in mice impairs decidualization, vascular remodeling, and formation of avascular primary decidua zone [ 119 ], highlighting that appropriate CB1 signaling has to be strictly regulated for pregnancy success.…”
Section: The Ecs: a Modulatory System For A Successful Pregnancymentioning
confidence: 99%
“…In fact, Li and colleagues recently found a significant retention of macrophages in the primary decidual zone of pregnant double CB1 −/− CB2 −/− mutant mice on GD 6, encircling the implantation chamber. The phenotype observed in double mutant mice was also recapitulated in CB1 deficient dams, but not in CB2 −/− mice, indicating an important role for CB1-mediated signaling in the local macrophage recruitment during early pregnancy [ 119 ].…”
Section: The Role Of Endocannabinoids In Low-grade Inflammation and M...mentioning
confidence: 99%